Waning Humoral Response 6 Month after Double Vaccination with the mRNA-BNT162b2 Vaccine in Hemodialysis Patients - Balčiuvienė, Vilma; Burčiuvienė, Asta; Haarhaus, Mathias; Uogintaitė, Jurgita; Janavičienė, Asta; Santockienė, Lina; Mitrikevičienė, Jurgita; Aleknienė, Loreta; Keinaitė, Danutė (Acta medica Lituanica, 2023)
Introduction: Although most hemodialysis patients (HDP) exhibit an initial seroresponse to vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), studies have shown this response to be lower compared to healthy subjects. This fact raised concerns regarding the durability of the immune response and effective protection against severe Coronavirus disease 2019 (COVID-19) in this vulnerable population. The aim of our study was to evaluate the change in antibody levels over time in HDP population. Materials and Methods: We performed a prospective multicenter study, evaluating antibody response among HDP at 2 and at 6 months after complete two-dose vaccination course with the mRNA-BNT162b2 (Pﬁzer-BioNTech) vaccine. The study was performed in 14 hemodialysis units of a private dialysis provider in Lithuania. The serum samples of 189 HDP were tested for SARS-CoV-2 IgG against the Spike glycoprotein. Results: 189 HDP participated in the study. Patients were 64.3±15.7 years of age, 116 (61.4%) were males and 73 (38.6%) were females. Among them, 183 (96.8%) were seropositive for anti-S IgG at 2 months after the second immunization dose. Six months after the second dose only 145 (76.7%) of study participants had positive anti-S IgG titers. The median level of anti-S IgG titers after 2 months was 383.1 BAU/mL (166.2–995.6) and after 6 months this level significantly decreased to 51.4 BAU/mL (22.0–104.0) (p<0.001). Seroresponses at both time points inversely correlated with increasing patient’s age. Risk factor for absent response after 2 months included oncologic disease. Systemic autoimmune disease and a history of myocardial infarction increased risk to be seronegative 6 months after the second vaccine dose. Conclusions: The majority of hemodialysis patients seroresponded after BNT162b2/Pfizer vaccination, but vaccine-induced humoral immunity wanes over time.